2017
DOI: 10.1136/oemed-2016-104119
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of malignant mesothelioma in women: gender differences and modalities of asbestos exposure

Abstract: IntroductionThe epidemiology of gender differences for mesothelioma incidence has been rarely discussed in national case lists. In Italy an epidemiological surveillance system (ReNaM) is working by the means of a national register.MethodsIncident malignant mesothelioma (MM) cases in the period 1993 to 2012 were retrieved from ReNaM. Gender ratio by age class, period of diagnosis, diagnostic certainty, morphology and modalities of asbestos exposure has been analysed using exact tests for proportion. Economic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 26 publications
4
44
1
1
Order By: Relevance
“…Moreover, in our cohort one year's environmental exposure was enough to be associated with MM, which is consistent with the literature; a dose-effect relationship between asbestos exposure and MM has been recognized but no minimum threshold of exposure to asbestos identified (25)(26)(27). The disease latency varies from one to seven decades, but the median latency is higher than observed in previous studies (28,29). Latency depends on exposure intensity and duration as well as unknown factors that probably are genetic (2).…”
Section: Panou Et Alsupporting
confidence: 91%
“…Moreover, in our cohort one year's environmental exposure was enough to be associated with MM, which is consistent with the literature; a dose-effect relationship between asbestos exposure and MM has been recognized but no minimum threshold of exposure to asbestos identified (25)(26)(27). The disease latency varies from one to seven decades, but the median latency is higher than observed in previous studies (28,29). Latency depends on exposure intensity and duration as well as unknown factors that probably are genetic (2).…”
Section: Panou Et Alsupporting
confidence: 91%
“…Non‐occupational exposure occurs predominantly in women . The three cases presented here echo the analysis of female mesothelioma cases in Italy where the important role of non‐occupational exposure was shown . With the cessation of asbestos mining, milling, and manufacturing of asbestos‐containing products it is expected that occupationally acquired cases of mesothelioma will decline.…”
Section: Discussionsupporting
confidence: 67%
“…A sex difference in asbestos-related mesothelioma cases has been reported. The rates of women with mesothelioma are lower than those of men as more men than women were exposed through their occupations [6].…”
Section: Introductionmentioning
confidence: 99%
“…Marinaccio and colleagues1 compared asbestos exposures of men and women with mesothelioma in Italy and found that women were less likely to have had occupational exposures and more likely to have experienced non-occupational and familial exposures. They did not consider possible asbestos exposures arising from the use of talcum powders, an exposure common in North America, that may have been in Italy as well.…”
mentioning
confidence: 99%